Genetic Architecture of Olfactory Behavior in Drosophila melanogaster: Differences and Similarities Across Development. - Lavagnino, N.J.; Arya, G.H.; Korovaichuk, A.; Fanara, J.J. (Behavior Genetics, 2013)
In the holometabolous insect Drosophila melanogaster, genetic, physiological and anatomical aspects of olfaction are well known in the adult stage, while larval stages olfactory behavior has received some attention it has been less studied than its adult counterpart. Most of these studies focus on olfactory receptor (Or) genes that produce peripheral odor recognition. In this paper, through a loss-of-function screen using P-element inserted lines and also by means of expression analyses of larval olfaction candidate genes, we extended the uncovering of the genetic underpinnings of D. melanogaster larval olfactory behavior by demonstrating that larval olfactory behavior is, in addition to Or genes, orchestrated by numerous genes with diverse functions. Also, our results point out that the genetic architecture of olfactory behavior in D. melanogaster presents a dynamic and changing organization across environments and ontogeny.